The minimally invasive total hip replacement via the direct anterior approach: A short term clinical and radiological results - Helmy Fekry Refai; Mohamed Samir Kassem (Alexandria Journal of Medicine, 2014)
Introduction: There has been a recent interest in the minimally invasive approaches for hip replacements. The direct anterior approach is characterised by being a muscle preserving approach which should make it an ideal minimally invasive approach. Aim: The purpose of this study was to assess the short term results and the complications of primary total hip replacements done through this approach. Methods: This study included twenty uncemented primary hip replacements done in eighteen patients. The average age at the time of surgery was 71.5 years and the average body mass index was 22.5. The period of follow up ranged from 26 to 43 months. Results: The length of hospital stay ranged from 3 days up to 19 days with a median of 5 days. Trendelenberg test was negative in 18 cases (90%). The Oxford hip score improved from a median of 16.5 preoperatively to a median of 40.5 postoperatively which was statistically significant (p < 0.001). Radiographically, seventeen hips (85%) had no malalignment of the stem with neutral position, and the cup version ranged from 14° to 45° of anteversion with a median of 26° whilst the cup abduction angle ranged from 35° to 63° with a median of 46.5. The complications included hyposthesia at the lateral cutaneous nerve of the thigh distribution in four cases (20%), partial femoral nerve palsy in one case, one early postoperative dislocation and one femoral shaft penetration. Conclusion: Total hip replacement through the direct anterior approach can offer an early good functional recovery with a short hospital stay. It may be associated with specific complications related to the approach which the surgeon should be aware of; especially in the start of his learning curve of the approach.